FDI Spillovers in Chinese Urban Agglomerations: Comparative Analysis of the Yangtze River Delta and the Pearl River Delta - Yuyuan WEN (European Regional Science Association (ERSA), 2014)
Using panel data covering 25 cities in the Yangtze River Delta (YRD) and 21 cities in the Pearl River Delta (PRD) over the 1991-2010 period, the paper applies spatial Durbin model with ML estimation techniques to examine the underlying relationship between the productivity of the host cities and FDI spillovers. The main findings are as follows. First, significant positive impacts of FDI on the local city's growth exist and increase over time, while spatial spillovers of FDI on growth present significantly but behave oppositely in YRD and PRD. Second, spatial interaction plays an important and non-negligible role in urban productivity growth; however, in the long term, YRD and PRD have significant but opposite spatial effects of growth. Third, inclusion of FDI raises the speed of conditional convergence of economic growth in YRD and PRD (for the case of single-regime). Fourth, positively spatial spillover of growth occurs in both regimes of YRD, while negatively spatial spillover for the case of PRD. The results here suggest important policy implications for the two regions to attract FDI and promote urban development.
Keywords: C31; F21; F23; 330; FDI; spillovers; spatial Durbin model; Yangtze River Delta; Pearl River Delta